Exposure of belt and road economies to China trade shocks - Bastos, Paulo (2020)
This paper uses international trade data to assess the degree of exposure of Belt and Road economies to China trade shocks. It ﬁnds that the growth of China’s trade following its internal transformation and accession to the WTO signiﬁcantly impacted the export performance of Belt and Road economies in the period 2000-2015. The increase in China’s imports signiﬁcantly boosted the exports of these economies. However, this e↵ect was attenuated by increased competition from China in export markets. The e↵ects of China’s demand shocks were stronger in more upstream industries, while those of competition shocks were stronger in industries that produce goods that are closer to ﬁnal use. The e↵ects of competition shocks were also relatively stronger in countries that are relatively poorer and geographically closer to China. Building on these ﬁndings, the paper documents the current degree of exposure of Belt and Road economies to China trade shocks.